What is the effectiveness of the support worker role for people with dementia and their carers? A systematic review. Issue 1 (December 2016) - Goeman, Dianne; Renehan, Emma; Koch, Susan
Abstract Background Dementia is progressive in nature and the associated functional decline inevitably leads to increasing dependence on others in areas of daily living. Models of support have been developed and implemented to assist with adjusting to living with memory loss and functional decline; to navigate the health and aged care system; and to access services. We undertook a systematic review of international literature on key worker type support roles to identify essential components and ascertain how the role can be best utilised to assist community-dwelling people with dementia and their carers. This review of support roles is the first to our knowledge to include both quantitative and qualitative studies and all models of support. Method A systematic review of studies written in English and published between January 2003 and December 2014. Data sources were Medline, PsychInfo and CINAHL, internet, expert consultation and reference lists of included studies. After screening articles to ensure that they reported on a key worker type support role, involved carers and or people with dementia living at home and removing duplicates, eligible papers were appraised and evaluated. Results Thirty six studies were eligible for inclusion in the review. Eligible studies were divided into type of support roles and study type. The heterogeneity of included studies and high risk of bias made a meta-analysis inappropriate and it was therefore difficult to draw overall conclusions. However, essential components shared across support worker models that demonstrated a positive impact on carer burden and improved quality of life included: long term intervention, face to face contact, individualised education and support based on needs, multi-disciplinary teams, collaborative input, health/clinical background of support workers, ongoing follow up and inter professional and inter-sectoral collaborations. There was a lack of studies assessing cost-effectiveness. Conclusions Studies that include a high quality evaluation of holistic, tailored models of support that identify which components of support produce the most valuable outcomes to assist people with dementia and their carers and families to continue to live meaningful lives are needed. There is also a need for a cost effectiveness evaluation of support worker roles. Trial registration PROSPERO international prospective register of systematic reviews: PROSPERO 2014CRD42014013992 .